SCIENTIFIC AND METHODOLOGICAL PROBLEMS OF THE DEVELOPMENT OF THE NATIONAL SPORT OF WRESTLING - Xujomov Bobomurod (Journals Park Publishing, 2022)
The article discusses the main scientific and methodological problems of training Greco-Roman style wrestlers. The author proposes a system for controlling the training process based on optimizing the parameters of technical actions and using special technical devices with feedback.
Keywords: management, system, training, technique, tactics, skill, highly qualified athletes, three-component training system, sports exercises